An intelligent orientation aid for the visually handicapped - Tan, Mitchell Rong Ern (2018)
Since the advent of the positioning satellites in the 1970s, much have evolved in the wide use of these satellites for outdoor navigation purposes and now the positioning evolution has moved to indoor navigation. Whilst the positioning satellites systems, like the Global Positioning Satellites (GPS) or GLONASS have worked well for outdoor navigation but it lagged in performance for indoor navigation due to the obstructions to the lines of sight to the positioning satellites.